Is the prophylaxis of patent ductus arteriosus useful in extremely premature infants? - Bersani, Iliana; De Carolis, Maria Pia; Lacerenza, Serafina; De Rosa, Gabriella; Fusco, Francesca Paola; Cota, Francesco; Romagnoli, Costantino (The Turkish Journal of Pediatrics, 2011)
This study was aimed to verify the efficacy and safety of ibuprofen prophylaxis of patent ductus arteriosus in very preterm infants, in order to select infants receiving higher benefits from this intervention. Two hundred neonates with gestational age (GA) < or = 28 weeks receiving ibuprofen within the first two hours of life were included. Ductus closure rate was 68%, and results were significantly dependent on GA (48.8% among neonates with GA < 26 weeks vs 73.2% among those with GA > or = 26 weeks, p < 0.01). Neonates with GA < 26 weeks showed a lower ductus closure after the primary course of therapy (20% vs 57.5%, p < 0.01), as well as higher reopening rate (16.2% vs 3.8%, p < 0.05) and need for surgical ligation (38.8% vs 5.8%, p < 0.01). During the prophylaxis period, 11 neonates (5.5%) showed pulmonary hypertension. Considering risks/benefits, we recommend prophylaxis only in infants with GA < 26 weeks.